Assessment of Sea-Turtle Status and Trends : Integrating Demography and Abundance (National Academies Press, 2010)
"All six species of sea turtles found in U.S. waters are listed as endangered or threatened, but the exact population sizes of these species are unknown due to a lack of key information regarding birth and survival rates. The U.S. Endangered Species Act prohibits the hunting of sea turtles and reduces incidental losses from activities such as shrimp trawling and development on beaches used for nesting. However, current monitoring does not provide enough information on sea turtle populations to evaluate the effectiveness of these protective measures. Sea Turtle Status and Trends reviews current methods for assessing sea turtle populations and finds that although counts of sea turtles are essential, more detailed information on sea turtle biology, such as survival rates and breeding patterns, is needed to predict and understand changes in populations in order to develop successful management and conservation plans."--Publisher's description.